Alterations in superoxide dismutase activity due to heterologous gene expression: plant peculiarities - Sakhno, L.O. (Фактори експериментальної еволюції організмів, 2015)
Aims. The analysis of the information about the features of transgenic plants bearing some genes which influenced on
the activity of one from enzymes of plant antioxidant defence, namely superoxide dismutase, was the aim. Results.
The review presents and summarizes the literature and own data reflecting physiological, biochemical and molecular
biological parameters of plants possessing higher or lower superoxide dismutase activity due to transgenesis. Conclusions.
Transgenic plants having the increased SOD activity would demonstrate no phenotype changes under favourable
conditions (or these changes have not been studied). But often they produced larger biomass and were characterized by
higher vegetative growth rate, higher total soluble protein and changed chlorophyll content in comparison with wild type
ones and/or transgenic plants bearing only empty vector. For most of them the improved tolerance to stresses of different
origin has been proved in laboratory and field trials. Biotechnological plants characterizing by increased SOD activity in
non-stressed conditions may have higher adaptive capacity compared ones possessing lowered SOD activity.
Keywords: SOD activity, transgenic plants, favourable conditions, stress.